Multitrophic interactions in cassava, Manihot esculenta, cropping systems in the subhumid tropics of West Africa - Schulthess, F.; Neuenschwander, Peter; Gounou, S. (1997)
The effect of fertilizer and mulch across tropic level of the cassava ecosystem, i.e. the plant, the cassava mealybug(CM), the wasp Apoanagyrus lopezi and its hyperparasitoids, was studied in two field experiments planted ins southern Benin. Several cassava cultivars with different branching patterns and varying susceptibility to the cassava mealbug were planted on a sandy loamy and a sandy soil, respectively. Four to seven months after application of the soil treatments, differences in N.P.K in the first 50cm of the soil had mostly disappeared, indicating that the soil nutrients had been taken up by the plant and/or had leached to deeper layers of the soil.